Low-dielectric polybenzoxazine resin and preparation method thereof

By introducing low molecular polarization density and rigid fluorine-containing bisphenol into the resin matrix, the main chain benzooxazine resin is prepared, which solves the problem of high dielectric properties of traditional resins, and achieves the characteristics of low dielectric, high temperature resistance and high strength, and is suitable for high frequency and high speed communication and radar radomes.

CN119613647APending Publication Date: 2025-03-14THE RES INST FOR SPECIAL STRUCTURES OF AERONAUTICAL COMPOSITE AVIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411828394.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing resin matrix is ​​difficult to meet the requirements of high-frequency and high-speed communication and radar radome wave transmission performance, especially in terms of 5G communication and weapon equipment performance improvement, traditional resins have a high dielectric performance, which is difficult to meet the requirements of low dielectric constant and loss tangent.

Method used

By introducing low molecular polarization density and rigid fluorobisphenol, the main chain benzooxazine resin was prepared, and the benzooxazine resin intermediate was synthesized by a one-step method, and the curing reaction was carried out at 100-220°C to obtain a low dielectric polybenzooxazine resin.

Benefits of technology

It realizes the low dielectric, high temperature resistance and high strength characteristics of the resin matrix, has excellent low dielectric characteristics, high glass transition temperature and high mechanical strength, and is suitable for copper clad plates and wave-transmitting composite materials, with a wide range of application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184939420000031
    Figure BDA0005184939420000031
  • Figure BDA0005184939420000032
    Figure BDA0005184939420000032
  • Figure BDA0005184939420000033
    Figure BDA0005184939420000033
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer resin synthesis, and relates to a low-dielectric polybenzoxazine resin and a preparation method thereof.The low-dielectric polybenzoxazine resin is prepared by adding a formaldehyde polymer, dihydric phenol, a monohydric phenol compound and hexamethylenediamine into a reactor, then adding a solvent into the reactor, reacting at 85-110 DEG C for 8-12 h, and after the reaction is finished, performing reduced pressure distillation to obtain the low-dielectric polybenzoxazine resin. The preparation method comprises the following steps: adding a certain amount of a solvent into a reaction solution, distilling out a certain amount of the solvent from the reaction solution, then pouring the reaction solution into an alcohol solvent to generate a precipitate, removing a supernatant to obtain a precipitate, drying the precipitate, grinding the dried precipitate to obtain benzoxazine intermediate powder, and carrying out a curing reaction on the benzoxazine intermediate at 100-220 DEG C for 8-16 hours to obtain the polybenzoxazine resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer resin synthesis, and relates to a fluorine-containing low dielectric constant, low dielectric loss tangent, high temperature resistant benzoxazine intermediate and polybenzoxazine resin for a wave-transmitting composite material skin and a copper clad laminate (CCL), and a preparation method thereof. Background Art

[0002] At present, with the rapid development of communication technology, people are moving from the Internet to the Internet of Things to realize the interconnection of all things, requiring electromagnetic signals to have faster propagation speed and better propagation quality. The transmission rate and transmission stability of electromagnetic signals are closely related to the dielectric properties of the substrate material in the printed circuit board (PCB). In the military field, the radar antenna cover is a component that integrates wave transmission, load bearing, heat insulation and other multi-functions. It protects the communication, telemetry, guidance and detonation systems of the aircraft to work normally under harsh environmental conditions. The dielectric properties of the resin matrix, as an important component of the composite material, directly affect the final dielectric properties of the wave-transmitting composite material. At present, the matrix resin of the traditional copper clad laminate is mainly epoxy resin, and the matrix resin of the radar antenna cover is mainly cyanate resin. However, the dielectric properties of the two are difficult to meet the requirements of high-frequency and high-speed communication and radar antenna cover wave transmission performance. In order to meet the requirements of high-frequency and high-speed 5G communication and improve the performance of weapons and equipment, it is urgent to develop a matrix resin material with lower dielectric properties. In order to solve the above problems, three types of matrix resins with low dielectric properties have been developed at home and abroad: (1) Polytetrafluoroethylene resin (PTFE), whose symmetrical molecular chain and high fluorine content give PTFE excellent dielectric properties. At 10GHz, its dielectric constant is 2.2 and its dielectric loss is 0.0007. However, PTFE is limited in its application due to its own shortcomings: the surface is inert, it is difficult to activate, it is difficult to combine with copper foil, and the adhesion is poor; the glass transition temperature (Tg) is low, the thermal expansion is large, and the yield of fine circuit processing is very low; and the mechanical properties are insufficient, such as the tensile strength and modulus of PTFE are very low, and the hardness is also low. (2) Hydrocarbon (PCH) resin is a polymer synthesized from unsaturated hydrocarbons containing vinyl or diene groups as monomers. The polymer is composed only of carbon and hydrogen elements, has low molecular polarity, and has a highly symmetrical molecular structure, so it has excellent low dielectric properties. At 1 GHz, its dielectric constant is less than 2.4 and its loss tangent is less than 0.005, which especially meets the requirements of 5G communication for low dielectric properties of high-frequency and high-speed copper-clad laminates. However, polyolefin resins have poor heat resistance and poor adhesion to metals, which is not conducive to the subsequent processing and molding of copper-clad laminates; (3) Polyphenylene ether resin (PPO), also known as polyphenylene oxide, is a linear non-crystalline high-temperature resistant thermoplastic resin prepared by oxidative coupling reaction of 2,6-dimethylphenol under the action of copper-ammonia complex catalyst. The large number of phenolic aromatic rings in its molecules increases the difficulty of molecular chain rotation, thereby increasing the rigidity of the molecular chain. In addition, there are no polar groups in PPO and the molecular structure is symmetrical, which makes PPO have a low dielectric constant of 2.47 and loss tangent. However, the current commercial PPO resins often have a high molecular weight, resulting in high melting temperature and melt viscosity, poor processing and molding, and no resistance to organic solvents, which limits the application of PPO.

[0003] Benzoxazine resin is a kind of heterocyclic compound called benzoxazine generated by Mannich reaction of phenol, formaldehyde and primary amine, which can be thermally ring-opened to form a cross-linked polybenzoxazine resin. It has the characteristics of high heat resistance, good flame retardancy, strong adhesion and low water absorption. The phenol-OH in polybenzoxazine often forms a large number of intramolecular hydrogen bonds with the tertiary amine on the Mannich bridge generated after ring opening, which reduces the content of free-OH in the resin, thereby reducing the polarity of the resin and giving the polybenzoxazine resin a lower dielectric property. At the same time, the presence of a large number of hydrogen bonds also makes the benzoxazine resin have a lower thermal expansion coefficient. However, the dielectric constant and loss tangent of the currently commonly used polybenzoxazine resin are still high, with the dielectric constant and loss tangent being about 2.8 and 0.01 respectively. Therefore, it is necessary to develop PBZ resins with low dielectric constant and loss tangent to meet the requirements of high electromagnetic wave permeability of wave-transmitting composite materials. At present, the main technical approaches for preparing low dielectric PBZ resins include copolymerization modification with other low dielectric polymers, addition of nanoparticles, and molecular structure design. Summary of the invention

[0004] Technical problem solved by the present invention: The present invention provides a low dielectric polybenzoxazine resin and a preparation method thereof, and prepares a main chain benzoxazine resin by introducing low molecular polarization density and rigid fluorinated bisphenol, thereby achieving the low dielectric, high temperature resistance and high strength characteristics of the resin matrix.

[0005] Technical Solution

[0006] A preparation method of a low-dielectric polybenzoxazine resin comprises: adding a formaldehyde polymer, a dihydric phenol, a monohydric phenol compound and hexamethylenediamine into a reactor, then adding a solvent into the reactor, reacting at 85-110°C for 8-12 hours, after the reaction is completed, distilling out a certain amount of the solvent from the reaction liquid by reduced pressure distillation, then pouring the reaction liquid into an alcohol solvent to generate precipitation, removing the upper clear liquid to obtain precipitation, drying the precipitation, grinding the dried precipitation to obtain a benzoxazine intermediate powder, and curing the benzoxazine intermediate at 100-220°C for 8-16 hours to obtain a polybenzoxazine resin.

[0007] Furthermore, the dihydric phenol is bisphenol H, bisphenol T or bisphenol D.

[0008] Further, the molecular formula of bisphenol H, bisphenol T or bisphenol D is as follows:

[0009]

[0010] Furthermore, the monophenol compound is phenol, p-tert-butylphenol or 4-trifluoromethylphenol, and the molecular structure is as follows:

[0011]

[0012] Further, the molecular structure of hexamethylenediamine is as follows:

[0013]

[0014] Furthermore, the solvent is any one or more of acetone, butanone, dioxane, ethanol, toluene and xylene.

[0015] Furthermore, the amount of solvent distilled from the reaction solution is not less than 85% of the amount of solvent added. If the amount of solvent distilled is less than 85%, the remaining solvent will change the solubility parameter of the alcohol solvent in the subsequent resin precipitation stage, resulting in the inability to fully precipitate the resin.

[0016] Furthermore, the alcohol solvent is any one or more of methanol, ethanol or isopropanol.

[0017] Furthermore, when the dihydric phenol used is bisphenol H, the generated benzoxazine intermediate is a bisphenol H type benzoxazine intermediate, and the molecular structure is:

[0018]

[0019] When the dihydric phenol used is bisphenol T, the generated benzoxazine intermediate is a bisphenol T-type benzoxazine intermediate, and the molecular structure is:

[0020]

[0021] When the dihydric phenol used is bisphenol D, the generated benzoxazine intermediate is a bisphenol D-type benzoxazine intermediate, and the molecular structure is:

[0022]

[0023] A low dielectric polybenzoxazine resin prepared according to the method.

[0024] Beneficial Effects

[0025] The present invention provides a low dielectric polybenzoxazine resin and a preparation method thereof. A benzoxazine resin intermediate is synthesized by a one-step method using formaldehyde polymer, dihydric phenol, monohydric phenol compound and hexamethylenediamine as raw materials, and the preparation process is simple. The benzoxazine resin intermediate can be melted at 80°C to 100°C, so it is melted by reacting at 85°C to 110°C for 8 to 12 hours, and the initial curing cross-linking temperature is 120 to 140°C, which has a wide processing window. Therefore, the present invention adopts a curing temperature of 100 to 220°C and reacts for 8 to 16 hours to obtain a solidified polybenzoxazine resin. The polybenzoxazine resin has excellent low dielectric properties, high glass transition temperature and high mechanical strength, and presents excellent comprehensive performance. Due to the high fluorine content of homemade diphenol, low molecular planning density and the introduction of large-volume end-capping groups such as tert-butyl and trifluoromethyl, polybenzoxazine resin has outstanding low electrical constants and loss tangents. It can be used as a resin matrix for copper-clad laminates or wave-transmitting composite materials, and has great application prospects in radar antenna covers, PCB substrates, 5G communication equipment and other fields. DETAILED DESCRIPTION

[0026] The present invention is further described below:

[0027] Embodiment 1:

[0028] A method for preparing a low dielectric polybenzoxazine resin comprises adding a formaldehyde polymer, a dihydric phenol (bisphenol H, bisphenol T or bisphenol D), a monohydric phenol compound (phenol, p-tert-butylphenol and 4-trifluoromethylphenol) and hexamethylenediamine into a reactor, adding a solvent, reacting at 85-110° C. for 8-12 hours, and after the reaction is completed, distilling the solvent from the reaction solution by low-pressure distillation to obtain a solvent amount not less than 85% of the added solvent amount, then pouring the reaction solution into an alcohol solvent to produce a precipitate, removing the supernatant to obtain a precipitate, drying the precipitate in a vacuum drying oven, and grinding the dried precipitate or using a pulverizer to obtain a benzoxazine intermediate, including bisphenol H type benzoxazine, bisphenol T type benzoxazine and bisphenol D type benzoxazine powder. The polybenzoxazine resin is a polybenzoxazine resin obtained by curing the benzoxazine intermediate at 100-220° C. for 8-16 hours.

[0029] Wherein, the diphenol is bisphenol H, bisphenol T or bisphenol D; the molecular formula of bisphenol H, bisphenol T or bisphenol D is as follows:

[0030]

[0031] Synthesis of bisphenol D: Under low temperature and acidic conditions, bis(trifluoromethyl)benzenediamine and sodium tetrafluoroborate are used as raw materials to obtain an intermediate. The intermediate is then reacted with trifluoroacetic acid at low temperature to obtain bisphenol D.

[0032] Synthesis of bisphenol T: Bisphenol T is synthesized using methoxyphenol, tetrafluorodibromoethane and pentafluorophenylborane as raw materials, sodium hydride and zinc powder as raw materials under a nitrogen atmosphere.

[0033] Synthesis of bisphenol H: Bisphenol H is synthesized by reacting trifluoroacetone derivatives with phenol in the presence of trifluoromethanesulfonic acid via a Friedel-Crafts reaction.

[0034] Among them, the monophenol compound is phenol, p-tert-butylphenol or 4-trifluoromethylphenol, and the molecular structure is as follows:

[0035]

[0036] The molecular structure of hexamethylenediamine is as follows:

[0037]

[0038] The solvent is any one or more of acetone, butanone, dioxane, ethanol, toluene and xylene; the alcohol solvent is any one or more of methanol, ethanol or isopropanol.

[0039] Among them, when the dihydric phenol used is bisphenol H, the generated benzoxazine intermediate is a bisphenol H type benzoxazine intermediate, and the molecular structure formula is:

[0040]

[0041] When the dihydric phenol used is bisphenol T, the generated benzoxazine intermediate is a bisphenol T-type benzoxazine intermediate, and the molecular structure is:

[0042]

[0043] When the dihydric phenol used is bisphenol D, the generated benzoxazine intermediate is a bisphenol D-type benzoxazine intermediate, and the molecular structure is:

[0044]

[0045] Example 2

[0046] Bisphenol H, hexamethylenediamine, p-tert-butylphenol and paraformaldehyde are added to a three-necked flask equipped with a condenser, the molar ratio of aldehyde, phenolic hydroxyl and amino functional groups is 2:1:1, and the molar ratio of phenolic hydroxyl functional groups in bisphenol H and p-tert-butylphenol is 1:1. Subsequently, a toluene:dioxane mixed solvent is added, wherein the volume ratio of toluene to dioxane is 2:1. The reaction is carried out at 90°C for 10 hours. After the reaction is completed, the solvent is distilled off under reduced pressure using a rotary evaporator until the amount of solvent distilled out is not less than 85% of the amount of solvent added. The reaction solution is poured into an alcohol solvent and allowed to stand for 12 hours. The upper solution is removed to obtain a precipitate. The precipitate is vacuum dried at 70°C for 48 hours. The dried product is ground and pulverized to obtain a bisphenol H type benzoxazine intermediate.

[0047] The yield of the benzoxazine intermediate in this example is 75.0%. The benzoxazine intermediate powder prepared above is placed in a mold, put into an oven, and cured at 100°C, 120°C, 140°C, 160°C, 180°C, and 190°C for 2 hours to obtain a polybenzoxazine resin having a glass transition temperature of 220°C, a compressive strength of 141.0 MPa, a flexural strength of 90.0 MPa, a dielectric constant of 2.60 at 10 GHz, and a dielectric loss of 0.003.

[0048] Example 3

[0049] Bisphenol T, hexamethylenediamine, phenol and paraformaldehyde are added to a three-necked flask equipped with a condenser, the molar ratio of aldehyde, phenolic hydroxyl and amino functional groups is 2:1:1, and the molar ratio of phenolic hydroxyl functional groups in bisphenol T and p-tert-butylphenol is 1:1. Then, a toluene:dioxane mixed solvent is added, wherein the volume ratio of toluene to dioxane is 2:1. The reaction is carried out at 90°C for 10 hours. After the reaction is completed, the solvent is distilled off under reduced pressure using a rotary evaporator until the amount of solvent distilled out is not less than 85% of the amount of solvent added. The reaction solution is poured into an alcohol solvent and allowed to stand for 12 hours. The upper solution is removed to obtain a precipitate. The precipitate is vacuum dried at 70°C for 48 hours. The dried product is ground and crushed to obtain a bisphenol T-type benzoxazine intermediate.

[0050] The yield of the benzoxazine intermediate in this example is 76.0%. The benzoxazine intermediate powder prepared above is placed in a mold, put into an oven, and cured at 100°C, 120°C, 140°C, 160°C, and 180°C for 2 hours to obtain a polybenzoxazine resin having a glass transition temperature of 198°C, a compressive strength of 120.0 MPa, a flexural strength of 80.0 MPa, a dielectric constant of 2.65 at 10 GHz, and a dielectric loss of 0.006.

[0051] Example 4

[0052] Bisphenol D, hexamethylenediamine, 4-trifluoromethylphenol and paraformaldehyde are added to a three-necked flask equipped with a condenser, the molar ratio of aldehyde, phenolic hydroxyl and amino functional groups is 2:1:1, and the molar ratio of phenolic hydroxyl functional groups in bisphenol D and p-tert-butylphenol is 1:1. Then, a toluene:dioxane mixed solvent is added, wherein the volume ratio of toluene to dioxane is 2:1. The reaction is carried out at 90°C for 10 hours. After the reaction is completed, the solvent is distilled off under reduced pressure using a rotary evaporator until the amount of solvent distilled out is not less than 85% of the amount of solvent added. The reaction solution is poured into an alcohol solvent and allowed to stand for 12 hours. The upper solution is removed to obtain a precipitate. The precipitate is vacuum dried at 70°C for 48 hours. The dried product is ground and crushed to obtain a bisphenol D type benzoxazine intermediate.

[0053] The yield of the benzoxazine intermediate in this example is 76.0%. The benzoxazine intermediate powder prepared above is placed in a mold, put into an oven, and cured at 100°C, 120°C, 140°C, 160°C, and 180°C for 2 hours to obtain a polybenzoxazine resin having a glass transition temperature of 198°C, a compressive strength of 120.0 MPa, a flexural strength of 95.0 MPa, a dielectric constant of 2.55 at 10 GHz, and a dielectric loss of 0.004.

[0054] Example 5

[0055] Bisphenol H, hexamethylenediamine, p-tert-butylphenol and paraformaldehyde are added to a three-necked flask equipped with a condenser, the molar ratio of aldehyde, phenolic hydroxyl and amino functional groups is 2:1:1, and the molar ratio of phenolic hydroxyl functional groups in bisphenol H and p-tert-butylphenol is 1:1. Subsequently, a toluene:ethanol mixed solvent is added, wherein the volume ratio of toluene to ethanol is 2:1. The reaction is carried out at 90°C for 10 hours. After the reaction is completed, the solvent is distilled off under reduced pressure using a rotary evaporator until the amount of solvent distilled out is not less than 85% of the amount of solvent added. The reaction solution is poured into an alcohol solvent and allowed to stand for 12 hours. The upper solution is removed to obtain a precipitate. The precipitate is vacuum dried at 70°C for 48 hours. The dried product is ground and pulverized to obtain a bisphenol H type benzoxazine intermediate.

[0056] The yield of the benzoxazine intermediate in this example is 69.0%. The benzoxazine intermediate powder prepared above is placed in a mold, put into an oven, and cured at 100°C, 120°C, 140°C, 160°C, 180°C, and 190°C for 2 hours to obtain a polybenzoxazine resin having a glass transition temperature of 220°C, a compressive strength of 141.0 MPa, a flexural strength of 90.0 MPa, a dielectric constant of 2.60 at 10 GHz, and a dielectric loss of 0.003.

[0057] Example 6

[0058] Bisphenol D, hexamethylenediamine, 4-trifluoromethylphenol and paraformaldehyde are added to a three-necked flask equipped with a condenser, the molar ratio of aldehyde, phenolic hydroxyl and amino functional groups is 2:1:1, and the molar ratio of phenolic hydroxyl functional groups in bisphenol D and p-tert-butylphenol is 1:1. Then, an acetone: butanone mixed solvent is added, wherein the volume ratio of acetone to butanone is 2:1, and the reaction is carried out at 70°C for 10 hours. After the reaction is completed, the solvent is distilled under reduced pressure using a rotary evaporator until the amount of solvent distilled out is not less than 85% of the amount of solvent added. The reaction solution is poured into an isopropanol solvent and allowed to stand for 12 hours. The upper solution is removed to obtain a precipitate, and the precipitate is vacuum dried at 70°C for 48 hours. The dried product is ground and pulverized to obtain a bisphenol D-type benzoxazine intermediate.

[0059] The yield of the benzoxazine intermediate in this example is 78.0%. The benzoxazine intermediate powder prepared above is placed in a mold, put into an oven, and cured at 100°C, 120°C, 140°C, 160°C, and 180°C for 2 hours to obtain a polybenzoxazine resin having a glass transition temperature of 198°C, a compressive strength of 120.0 MPa, and a flexural strength of 95.0 MPa.

[0060] The present invention provides a low dielectric polybenzoxazine resin and a preparation method thereof. A benzoxazine resin intermediate is synthesized by a one-step method using formaldehyde polymer, dihydric phenol, monohydric phenol compound and hexamethylenediamine as raw materials, and the preparation process is simple. The benzoxazine resin intermediate can be melted at 80°C to 100°C, so it is melted by reacting at 85°C to 110°C for 8 to 12 hours, and the initial curing cross-linking temperature is 120 to 140°C, which has a wide processing window. Therefore, the present invention adopts a curing temperature of 100 to 220°C and reacts for 8 to 16 hours to obtain a solidified polybenzoxazine resin. The polybenzoxazine resin has excellent low dielectric properties, high glass transition temperature and high mechanical strength, and presents excellent comprehensive performance. Due to the high fluorine content of homemade diphenol, low molecular planning density and the introduction of large-volume end-capping groups such as tert-butyl and trifluoromethyl, polybenzoxazine resin has outstanding low electrical constants and loss tangents. It can be used as a resin matrix for copper-clad laminates or wave-transmitting composite materials, and has great application prospects in radar antenna covers, PCB substrates, 5G communication equipment and other fields.

Claims

1. A method for preparing a low dielectric polybenzoxazine resin, characterized in that: include: Add formaldehyde polymer, dihydric phenol, monohydric phenol compound and hexamethylenediamine into a reactor, then add solvent into the reactor, react at 85-110°C for 8-12h, after the reaction is finished, distill a certain amount of solvent from the reaction liquid by reduced pressure distillation, then pour the reaction liquid into an alcohol solvent to generate precipitation, remove the upper clear liquid to obtain precipitation, dry the precipitation, grind the dried precipitation to obtain benzoxazine intermediate powder, and cure the benzoxazine intermediate at 100-220°C for 8-16h to obtain polybenzoxazine resin.

2. The method for preparing a low dielectric polybenzoxazine resin according to claim 1, characterized in that: The diphenol is bisphenol H, bisphenol T or bisphenol D.

3. The method for preparing a low dielectric polybenzoxazine resin according to claim 2, characterized in that: The molecular formula of bisphenol H, bisphenol T or bisphenol D is as follows:

4. The method for preparing a low dielectric polybenzoxazine resin according to claim 3, characterized in that: The monophenolic compound is phenol, p-tert-butylphenol or 4-trifluoromethylphenol, and the molecular structure is as follows:

5. The method for preparing a low dielectric polybenzoxazine resin according to claim 4, characterized in that: The molecular structure of hexamethylenediamine is as follows:

6. The method for preparing a low dielectric polybenzoxazine resin according to claim 5, characterized in that: The solvent is any one or more of acetone, butanone, dioxane, ethanol, toluene and xylene.

7. The method for preparing a low dielectric polybenzoxazine resin according to claim 6, characterized in that: The amount of solvent distilled out from the reaction solution is not less than 85% of the amount of solvent added.

8. The method for preparing a low dielectric polybenzoxazine resin according to claim 7, characterized in that: The alcohol solvent is any one or more of methanol, ethanol or isopropanol.

9. The method for preparing a low dielectric polybenzoxazine resin according to claim 8, characterized in that: When the dihydric phenol used is bisphenol H, the generated benzoxazine intermediate is a bisphenol H type benzoxazine intermediate, and the molecular structure is: When the dihydric phenol used is bisphenol T, the generated benzoxazine intermediate is a bisphenol T-type benzoxazine intermediate, and the molecular structure is: When the dihydric phenol used is bisphenol D, the generated benzoxazine intermediate is a bisphenol D-type benzoxazine intermediate, and the molecular structure is:

10. A low dielectric polybenzoxazine resin prepared according to the method of claim 9.